Inclusion initiated fracture under cyclic torsion very high cycle fatigue at different load ratios. (May 2019) - Karr, Ulrike; Schönbauer, Bernd; Fitzka, Michael; Tamura, Eichi; Sandaiji, Yusuke; Murakami, Shogo; Mayer, Herwig
Highlights: Ultrasonic torsion fatigue tests at positive load ratios are described. Inclusion initiated fracture is found for cyclic torsion at positive load ratios. Exclusively surface fracture is found for fully reversed cyclic torsion. Load ratio influences the cyclic torsion HCF and VHCF strength or spring steel. Interface fracture at aluminates and fracture of MnS inclusions initiated cracks. Abstract: The influence of inclusions on cyclic torsion very high cycle fatigue (VHCF) is studied at different load ratios. Testing material is a high-strength spring steel, which was prepared based on the SWOSC–V composition with intentionally increased number and size of inclusions. Ultrasonic torsion fatigue tests were performed at load ratios R = –1, R = 0.1 and R = 0.35 with shot peened specimens. All specimens that were cycled at R = 0.1 or R = 0.35 and failed above 10 8 cycles showed crack initiation at internal aluminate or MnS inclusions. Interface failures between particles and metallic matrix generate cracks at aluminate inclusions, which predominantly grow in mode I. MnS inclusions have an elongated shape oriented in the specimens' length direction. Shearing of the MnS inclusions generates initial mode II/mode III cracks, which subsequently branch to mode I cracks. All specimens cycled at R = –1 showed surface crack initiation without inclusions, irrespective of lifetime. S–N curves are shifted towards lower shear stress amplitudes with increasing load ratio, indicating a pronounced mean stress influence on cyclic torsion strength.